Analysis Of Inpatient Medical Record Service Management Based On Medical Record Service Standards Between General Hospital Royal Prima Medan And Royal Prima Marelan - Hasibuan, Nasyidah Hannum; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Abstract. Inpatient medical records play a crucial role as a source of data and health information for inpatients, supporting their treatment and care planning. One of the main factors contributing to is-sues in inpatient medical records management is the lack of discipline among those responsible for handling patients when filling out medical records. This can lead to discrepancies in inpatient medi-cal record management, preventing it from aligning with established medical record service stand-ards. The purpose of this study was to analyze the management of inpatient medical records based on medical record service standards. This research employed a quantitative analytical approach with a cross-sectional design. Data analysis was performed using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis with multiple logistic regression at a 95% confi-dence level (α=0.05α=0.05). The results indicated that the implementation of inpatient medical rec-ord management based on medical record service standards at Royal Prima Medan Hospital and Royal Prima Marelan Hospital was significantly influenced by work motivation (p=0.001p=0.001) and supervision (p=0.000p=0.000). Meanwhile, the variables that did not have a significant effect were length of service (p=1.000p=1.000), education (p=0.848p=0.848), and teamwork (p=0.241p=0.241). Among these, the supervision variable was the most dominant factor, with an Exp (B) / OR value of 19.542. It is recommended that hospital leadership enforce close supervision (waskat) for all medical record employees and provide motivation through seminars and training pro-grams to enhance the implementation of inpatient medical record management based on medical rec-ord service standards.